‘Policing Is a Profession of the Heart’: Evangelicalism and Modern American Policing - Griffith, Aaron (Religions, 2021)
Though several powerful explorations of modern evangelical influence in American politics and culture have appeared in recent years (many of which illumine the seeming complications of evangelical influence in the Trump era), there is more work that needs to be done on the matter of evangelical understandings of and influence in American law enforcement. This article explores evangelical interest and influence in modern American policing. Drawing upon complementary interpretations of the “antistatist statist” nature of modern evangelicalism and the carceral state, this article offers a short history of modern evangelical understandings of law enforcement and an exploration of contemporary evangelical ministry to police officers. It argues that, in their entries into debates about law enforcement’s purpose in American life, evangelicals frame policing as both a divinely sanctioned activity and a site of sentimental engagement. Both frames expand the power and reach of policing, limiting evangelicals’ abilities to see and correct problems within the profession.